(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to such extremely important, but still not enough studied source from history of the Azov Cossacks, which the materials of Complete Collection of laws of the Russian empire are. There are annotations of the 71 documents, in which the Azov Cossack’s army, the Azov Cossacks are mentioned.